Tjatatan Mengenai Beberapa Hama Padi dari Indonesia - Soelaksono Sastrodihardjo (Journal of Mathematical and Fundamental Sciences, 1970)
Ringkasan. Dari sedjumlah besar binatang jang berpotensi sebagai hama, hanja terdapat kurang dari sepuluh species jang betul-betul mempunjai arti ekonomi (hama). Penggerek batang (Tryporyza), walang sangit (Leptocirisa) dan tikus (Rattus) merupakan tiga hama utama dari padi. Ketiga hama ini dan hama padi lainnja jang kurang penting terdapat didaerah sawah diseluruh Indonesia. Penggerek batang seringkali mendjadi wabah (outbreaks) terutama didaerah utara dari pulau Djawa. Tikus mendjadi wabah baik didataran rendah maupun didataran tinggi, sedang "outbreaks" dari walang sangit terbatas didaerah utara Djawa Barat. Sebagai patokan dari "outbreaks" dipakai angka kerusakan 5000 IIA tanaman padi. Abstract. There are less than ten important rice crop pests out of a large number of general known pests. Rice stem borers (Tryporyza), rice bugs (Leptocorisa) and field rats (rattus) caused serious damages on rice crops. These three important pests and other less important ones were found at rice fields throughout Indonesia. The outbreaks of rice stem borers occurred at the northern part of Java almost yearly. The outbreaks of field rats were more widespread either at lowland or highland, whereas the outbreaks of the rice bugs were restricted to the northern part of West Java. The adapted value for outbreaks was 5000 HA damages on rice crop.